Customized production through 3D printing in cloud manufacturing - Zhang, Lin; Zhou, Longfei; Xiao, Luo (Elsevier, 2023)
Customized Production Through 3D Printing in Cloud Manufacturing explains how to combine the latest cloud manufacturing and additive manufacturing technology to find innovative solutions to important problems in research and industry. The manufacturing industry strives constantly to improve levels of product personalization for its customers, who have become increasingly demanding in this respect in recent decades. Among the tools currently growing in use in the industry, there is great potential to address this demand. Cloud manufacturing maps manufacturing resources and capabilities to the cloud, adding the capacity to gather decentralized manufacturing resources and use manufacturing services on-demand, and 3D printing provides strong support for truly individualized manufactured components. This is the first book to cover the whole lifecycle of 3D printing services in a cloud environment, including topics like: cloud servitization of 3D printers, 3D printing model design, supply-demand matching and scheduling, on-demand using and pricing, printing monitoring in cloud, and printing service evaluation. With a systematic introduction to this promising manufacturing paradigm, as well as coverage of models and service management to practical applications, this book will meet the needs of a broad range of researchers as well as practitioners.